Assessing equity in adult social care: An empirical analysis of resource allocation and ethnic disparities in Bradford - Novaes, Juliana (International Journal of Population Data Science, 2025)
The study provides an empirical data analysis to assess equity in the provision of adult social care (ASC) services in different Lower layer Super Output Areas (LSOAs) in Bradford. It examines patterns in the use of council-funded ASC to measure equity by identifying potential disparities in the allocation and distribution of resources of the system by different ethnic groups. This paper aims to evaluate equity in ASC service provision by estimating demand (need) and supply (usage) at neighborhood level. Demand is microsimulated using the English Longitudinal Study on Aging (ELSA) and Census. Supply is quantified from a customer-level dataset on ASC service from Connected Bradford using an adapted Recency Frequency Monetary model. The study uses risk ratios to verify if council-funded care is being supplied proportionally to the estimated demand, exploring how the demographic component of ethnicity relates to the need and usage of care at neighborhood level. The results draw two key conclusions. The first reveals inequity in distribution of resources among LSOAs, with 20% of the neighborhoods showing deviation from equitable provision, with either higher or lower rates of service supply than expected based on the estimated demand. The second points to potential disparities in accessing ASC services among different ethnic groups. In the 40 neighborhoods where the service supply highly exceeds the demand, there is a disproportionally higher number of white patients than would be expected given the demographics of the LSOA, with risk ratios consistently above 1. Conversely, in areas where supply is significantly lower than expected, there is more representation of patients of black ethnicity. Asian patients are underrepresented, with risk ratios below 1 in most areas. The results underscore a potential distortion in the provision of adult social care in Bradford, showing that resources are not distributed proportionally to need, suggesting also ethnic disadvantages in the domain of care. These discrepancies corroborate existing literature in the field and highlights challenges in achieving equitable service allocation in ASC.